Sex Determination (X and Y Chromosome) based on Histological Findings in Tooth: Literature Review - Riki Kristanto; Kadek Asri Asmita Pradnyana Putri; Ayu Bintang Rena Sanjiwani Budhiarta; Ista Prestiyanti; Putri Marina Marini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Odontology forensic is a branch of forensics science as well as dentistry that handles, examines, and evaluates dental evidence in effort of complying the interest of justice. The ability of dental evidence to be used as an identification tool is very possible as the fact of how durable teeth are. There are several methods to examine the dental evidence in effort to conduct an identification. However, there are circumstances in which histological examination is the only method that can be conducted. This led to the aim of this study. To review histological examination in teeth as sex determination method and to discuss its exclusivity compared to other methods. This literature used journals and textbooks with keywords according to the topic of discussion. Data obtained from different search engines such as Google Scholar, PubMed, Springer and NCBI. A total of 27 journals and 3 textbooks skimmed and narrowed down in to the 12 journals and 1 textbook. Narrowing down the data are necessary as information attained are similar to avoid redundancy. There are two findings that are targeted when it comes to histological examination of the tooth in order to determine one’s sex. They are F bodies and Barr bodies. Both targets appear in sample obtained from the dental pulpal tissue. Further, histological examination as a sex determination method is critical to be develop. Especially in times whereas the other methods are not reliable enough due to limited sample inclusion and cost. It is important to understand histological examination in forensic dentistry.